Controversies in Surgical Treatment of Recalcitrant Plantar Fasciitis. Issue 2 (June 2021) - Cheney, Nicholas; Sharpe, Barry Dale; Lauf, Jason; Long, Joseph
Abstract : Plantar fasciitis is a common cause of heel pain that is seen by both orthopedic surgeons and primary care providers. It is a condition that was previously thought to be because of inflammation of the plantar fascia but has more recently been linked an equinus contracture of the gastrocnemius muscle. The condition can be handled both conservatively and surgically, with the primary management being nonoperative. For operative interventions, the treatment of choice was classically a plantar fasciotomy. Over the past several years, the gastrocnemius recession has become an operative treatment of choice. The gastrocnemius recession has shown better symptom relief with less morbidity. The technique to perform a gastrocnemius recession is described within the chapter, as well as the postoperative management. In the future, the duration of nonoperative management for recalcitrant disease may be reduced. However, more randomized control trials showing positive results of the gastrocnemius recession may allow for shorter nonoperative management period creating a new standard treatment algorithm. Level of Evidence: Diagnostic level I, systematic review of studies.